Case reportToriello-Carey syndrome – a report of two new cases with additional findings - Mousavi, Seyed A. (Archives of Medical Science, 2008)
Toriello-Carey syndrome is a rare multiple midline malformation. This report presents two patients with a new combination besides additional findings of clinical presentation and surgical management.